2021
DOI: 10.1186/s13048-021-00906-w
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG25 promotes the malignancy of endometrial cancer by sponging microRNA-497-5p and increasing FASN expression

Abstract: Background Small nucleolar RNA host gene 25 (SNHG25), a long noncoding RNA, has been well-studied in epithelial ovarian cancer. However, the specific functions of SNHG25 in endometrial cancer (EC) have not been studied yet. In this study, we aimed to elucidate the clinical significance of SNHG25 in EC and determine the regulatory activity of SNHG25 on the tumor-associated EC phenotype. We also thoroughly explored the molecular mechanisms underlying SNHG25 function in EC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Return to the role of SNHG25 in NB, we unveiled that SNHG25 depletion inhibited NB cell proliferation, invasion and migration. Our findings supported SNHG25 as a tumor-promotor in NB, consistent with its role reported in epithelial ovarian cancer [ 21 ] and endometrial cancer [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…Return to the role of SNHG25 in NB, we unveiled that SNHG25 depletion inhibited NB cell proliferation, invasion and migration. Our findings supported SNHG25 as a tumor-promotor in NB, consistent with its role reported in epithelial ovarian cancer [ 21 ] and endometrial cancer [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…As a typical miRNA, miR-497-5p’s contribution to suppressing tumor has been elaborated in many studies. 24–27 Previous studies also revealed miR-497-5p promoted radiosensitivity of breast cancer cells, 15 cervical cancer cells, 28 and esophageal squamous cell carcinoma cells. 29 Moreover, bioinformatics analysis suggested SMAD3 as a possible miR-497-5p target.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, the TF most significantly involved in FASN regulation, SREBF1, also plays an important role in lipid metabolism ( 45 , 46 ). Recent studies also reported that multiple lncRNAs competitively bind miRNAs to regulate FASN expression in nasopharyngeal and endometrial cancer ( 47 , 48 ). For drugs targeting FASN, a phase II clinical trial revealed that temsirolimus show potential benefit in bladder cancer patients who are refractory to first line platinum-based chemotherapy ( 49 ).…”
Section: Discussionmentioning
confidence: 99%